The Efficacy and Safety of the Combination Therapy With GLP-1 Receptor Agonists and SGLT-2 Inhibitors in Type 2 Diabetes Mellitus: A Systematic Review and Meta-analysis - Li, Chen; Luo, Jie; Jiang, Mingyan; Wang, Keke (Frontiers in Pharmacology, 2022)
Aims: Glucagon-like peptide-1 receptor agonists and sodium-glucose co-transporter-2 inhibitors play a key role in the treatment of type 2 diabetes mellitus. This meta-analysis aims to evaluate the efficacy and safety of their combination, emphatically focusing on the effects of treatment duration and add-on drugs. Methods: Seven databases were searched until June 2021 for randomized controlled trials with a duration of at least 12 weeks, evaluating the effects of combination therapy with glucagon-like peptide-1 receptor agonists and sodium-glucose co-transporter-2 inhibitors. Results: A total of eight eligible articles were included, pooling data retrieved from 1895 patients with type 2 diabetes mellitus. Compared to monotherapy, combination therapy resulted in a greater reduction in glycated haemoglobin (HbA1c), body weight, fasting plasma glucose (FPG), 2h postprandial glucose (2h PG), systolic blood pressure (SBP), body mass index (BMI) and low-density lipoprotein cholesterol (LDL-C). The decrease in HbA1c, body weight and FPG was maintained for more than 1 year, but these effects gradually regressed over time. The risk for hypoglycaemia was significantly increased with combination therapy. In addition, drug discontinuation, diarrhoea, injection-site-related events, nausea, vomiting and genital infections were more likely to occur in combination therapy. Conclusions: Glucagon-like peptide-1 receptor agonist and sodium-glucose co-transporter-2 inhibitor combination therapy showed superior effects on reducing HbA1c, body weight, FPG, 2h PG, SBP, BMI and LDL-C, without major safety issues, when compared with monotherapy in patients with type 2 diabetes mellitus.